Archaeomineralogy - Rapp, George R. author. aut Link
XI, 326 p. 68 illus.
Keywords: 1.1 Prologue What is archaeomineralogy? The term has been used at least once before (Mitchell 1985), but this volume is the first publication to lay down the scientific basis and systematics for this subdiscipline. Students sometimes call an introductory archaeology course "stones and bones." Archaeomineralogy covers the stones component of this phrase. Of course, archaeology consists of a great deal more than just stones and bones. Contemporary archaeology is based on stratigraphy, geomorphology, chronometry, behavioral inferences, and a host of additional disciplines in addition to those devoted to stones and bones. To hazard a definition: archaeomineralogy is the study of the minerals and rocks used by ancient societies over space and time, as implements, orna ments, building materials, and raw materials for ceramics and other processed products. Archaeomineralogy also attempts to date, source, or otherwise char acterize an artifact or feature, or to interpret past depositional alteration of archaeological contexts. Unlike geoarchaeology, archaeomineralogy is not, and is not likely to become, a recognized subdiscipline. Practitioners of archaeomineralogy are mostly geoarchaeologists who specialize in geology and have a strong background in mineralogy or petrology (the study of the origin ofrocks).